The academically destructive nature of trigger warnings. Issue 2 (2nd July 2016) - Vatz, Richard E.
Abstract: Trigger warnings are the latest concession to the notion espoused by some students and progressive professors that learning, particularly in higher education, should be pain-free psychologically. Such a premise is antithetical to the values of academic freedom and the marketplace of ideas and is inconsistent with students' learning and confronting ideas with which they are unfamiliar and which are outside of their comfort zone. Yielding to demands for trigger warnings when exposing students to ideas, topics and exchanges that may become uncomfortable negates growth for students. In short, acquiescing to the self-serving demands for trigger warnings makes education nothing but the reaffirming of ideas and positions with which students enter the academy. This article may upset undergraduates and progressive faculty and administrators…deal with it.